PENGARUH MINAT BELAJAR DAN PEMANFAATAN TEKNOLOGI TERHADAP HASIL BELAJAR SISWA KELAS X JURUSAN BISNIS DARING PEMASARAN DI SMK NEGERI 6 MEDAN T.A 2024/2025 - Grace Rimenda Bibra; Dionisius Sihombing (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of learning interest and technology utilization on the learning outcomes of class X students majoring in Online Business Marketing at SMK Negeri 6 Medan. The population in this study was 63 students. The sampling technique was carried out using a total sampling technique, so that the entire study population was used as a research sample, namely 63 students. Data collection instruments used were observation, questionnaires, and documentation. The data analysis technique used in this study was multiple linear regression analysis with hypothesis testing, namely Partial Test (T-Test), Simultaneous Test (F-Test), and Coefficient of Determination (R2). Based on the analysis that has been done, it was obtained that the results of learning interest have a positive and significant effect on learning outcomes, where the t-value was 6.153 with a significance of 0.000 <0.005. The variable of technology utilization also has a positive and significant effect on student learning outcomes where the t-value was 8.307 with a significance value of 0.000 <0.005. Simultaneously, the variables of learning interest and technology utilization significantly influenced learning outcomes, with an F-test value of 69.279 and a significance value of 0.000 < 0.005, indicating that the hypothesis is accepted.